COVID-19 and biologics in severe asthma: data from the Belgian Severe Asthma Registry. Issue 6 (3rd December 2020) - Hanon, Shane; Brusselle, Guy; Deschampheleire, Maud; Louis, Renaud; Michils, Alain; Peché, Rudi; Pilette, Charles; Rummens, Peter; Schuermans, Daniel; Simonis, Hélène; Vandenplas, Olivier; Schleich, Florence
Epidemiological studies suggest that patients with asthma are not at an increased risk of severe coronavirus disease 2019 (COVID-19) caused by the novel coronavirus severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) [1–3]. Recent studies indicate that the severity of COVID-19 in patients with asthma is likely to depend on multiple factors. A type 2-low asthma phenotype, use of oral corticosteroids and severe asthma could be aggravating factors, while maintenance treatment with inhaled corticosteroids (ICS) and good asthma control are probably protective [4]. However, there is currently scarce information on the risk associated with COVID-19 in subjects with severe asthma and/or the use of biologics. Since eosinopenia is a biomarker for the severity of COVID-19 [5], the eosinophil depletion induced by anti-IL5 and anti-IL5 receptor blocking monoclonal antibodies raises concern in patients and their treating physicians. In a cohort of severe asthma patients, a small number of COVID-19 cases was found; none resulted in death or a very severe disease course. Use of biologics for severe allergic or severe eosinophilic asthma was not associated with a higher risk of COVID-19. https://bit.ly/3ndZmyD